2011
DOI: 10.1007/s11105-011-0286-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modification of Soybean with a Novel Grafting Technique: Downregulating the FAD2-1 Gene Increases Oleic Acid Content

Abstract: A hairpin RNA-encoding construct targeting gmFAD2-1 was transformed into soybean, and an optimised Agrobacterium-mediated embryonic tip system was employed. A novel intergeneric grafting method using transgenic plantlets as scions was used instead of the conventional rooting method. Compared with traditional acclimatisation, the survival ratio of cleft grafts increased by 70%, and the culture period was shortened by about 40 days. The regeneration frequency of the grafted shoots in this embryonic tip system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Arabidopsis thaliana (Stoutjesdijk et al 2002), tobacco (Yang et al 2006), cotton plant , soybean (Chen et al 2011;Wagner et al 2011), rape (Jung et al 2011;Tian et al 2011) and rice (Zaplin et al 2013). Very recently, this approach was also reported in flax (Chen et al 2015).…”
Section: Modification Of Fatty Acid Content and Composition In Flaxmentioning
confidence: 92%
“…Arabidopsis thaliana (Stoutjesdijk et al 2002), tobacco (Yang et al 2006), cotton plant , soybean (Chen et al 2011;Wagner et al 2011), rape (Jung et al 2011;Tian et al 2011) and rice (Zaplin et al 2013). Very recently, this approach was also reported in flax (Chen et al 2015).…”
Section: Modification Of Fatty Acid Content and Composition In Flaxmentioning
confidence: 92%
“…Similar work done in variety Maverick using CRISPR, which resulted in dramatic increase in oleic acid content to over 80% and decrease in linoleic acid to 1.3-1.7% (Do et al, 2019). Double knockout of GmFAD2-1A (Glyma.10G278000) and GmFAD2-2B (Glyma.19G147300) in variety JN38 has resulted in increase of oleic acid content in seeds from 19.15% to 72.02%; decrease of linoleic acid from 56.58% to 17.27% in the T3 generation (Chen et al, 2011). Moreover, the percentage of protein in the seeds was increased from 37.52% to 40.58% (Wu et al, 2020).…”
Section: Modification Of Agronomy Traitsmentioning
confidence: 99%
“…Several approaches have been deployed to create mutations in members of the FAD2 gene family for the purpose of distinguishing which genes play the most significant role in determining oleic acid concentration in soybean seed. RNAi techniques 45,46) , Targeting Induced Lesions in Genomes (TILLING) strategies 47) , and the creation of deletion mutants via fast neutron radiation 48) have demonstrated that GmFAD2-1 genes convey major effects on oleic acid concentration in seed compared to GmFAD2-2 genes. Furthermore the members of these subclasses may be distinguished by comparative differences in SNP patterns within FAD2 gene sequences.…”
Section: Enhancing Global Food Security For High-oleic Vegetable Oilmentioning
confidence: 99%